Food properties handbook (CRC, 1995)
This book is a comprehensive treatment of the properties of foods. The theory and data presented can be applied to design food processing operations and to increase process efficiency and product quality. Each chapter contains definition of terminology, measurement techniques, experimental data, prediction models and application of the properties. Each chapter also contains worked out examples describing how to calculate the properties in different process conditions and food product composition